CALCULATION OF ELECTRONIC PROPERTIES AND MECHANICAL PROPERTIES OF CUBIC PHASE CH3NH(3)PbCl3 USING DENSITY FUNCTIONAL METHOD - Ong, Russell; Sagala, Junaina Sahputri (Universitas Negeri Medan, 2025)
Organic-inorganic hybrid halide perovskite-based solar cells such as CH3NH3PbCl3 are known to have many advantages such as low price, simple preparation process and high photoelectric conversion rate. Therefore, we performed theoretical calculations to determine the electronic properties and mechanical properties of CH3NH(3)PbCl3material with space group p3m3 with bulk system in this study. Both properties are calculated by the Density Functional Theory (DFT) method through Quantum ESPRESSO software. The electronic properties discussed include electronic band structure, density of states (DOS) curve, and projected density of state s (PDOS) curve, while the mechanical properties include elasticity constant (Cij), limb modulus (B), Young's modulus (E), shear modulus (G), and Poisson's ratio (ʋ). To determine these properties, the optimum lattice constant must be achieved through optimization of k-points and cut-off kinetic energy. The results show that the value of the lattice gap is 2.49 eV, and C11, C21, C44, limbal modulus, Young's modulus, shear modulus, and Poisson's ratio are 143.83 GPa, 21.22 GPa, 28.24 GPa, 62.09 GPa, 101.75 GPa, 41.47 GPa, and 0.23 GPa, respectively. This shows that the cubic phase CH3NH3PbCl3 waste material is mechanically stable which also has great potential as a perovskite semiconductor material.